The effect of addition protein, phosphatidylcholine, phosphatidylserine, and inulin on GFAP levels of acute ischemic stroke patients at Dr. Kariadi Hospital, Semarang - Wahyuningrum, Diah Retno; Retnaningsih, Retnaningsih; Kartasurya, Martha Irene (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: The occurrence of ischemia causes a loss of energy to switch to anaerobic processes resulting in acidosis due to reduced Adenosina Triphosphate (ATP). This condition makes neuron cells apoptotic. Apoptotic of several biochemical substrates in the brain, such as Glial Fibrillary Acidic Protein (GFAP) exit into the circulatory system which is associated with dysbiosis through immunological pathways.Objectives: To determine the effect of giving enteral formula containing protein, phosphatidylcholine, phosphatidylserine, and inulin on GFAP levels in patients with acute ischemic stroke Dr. Kariadi Hospital.Materials and Methods: This study was done in a single-blind RCT. Eighteen ischemic stroke patients were randomly divided into intervention (9 subjects) and control groups (9 subjects). The intervention group received 69 g of the powdered enteral formula three times a day for seven days. The formula contained protein (15 g), phosphatidylcholine (128 mg),  phosphatidylserine (32 mg), and inulin (3 g). The subject who had diabetes mellitus received for 14 days at a dose of 34.5 g per day (7.5 g protein with additions 64mg phosphatidylcholine, 16mg phosphatidylserine, 1.5 g inulin). The control group received the standard enteral formula from the hospital, which contains (11.8 g protein without additions protein, phosphatidylcholine, phosphatidylserine, and inulin). GFAP levels by ELISA method (Enzyme-linked immunosorbent Assay) at pre and post-intervention.Results: There was a trend of decreasing GFAP levels before and after in the intervention group towards a better direction from 8.37±4.25 to 8.30±4.9 compared with the control group which experienced an increasing trend from 5.4±1.8 to 7.5±4. There was no significant difference in GFAP levels after intervention between groups (p = 0.7).Conclusions: The addition of protein, phosphatidylcholine, phosphatidylserine, and inulin had no significant effect on GFAP levels.